Single Subject Research in Mathematics Education: Systematic Literature Review in The Indonesian Context - Arvianto, Ilham Rais; Nofiansyah, Wahyu; Fadila, Abi (Jurnal VARIDIKA, 2026)
Several literature reviews related to Single Subject Research (SSR) have been reported, but none have re-ported a systematic literature review of SSR in mathematics learning in Indonesia. Therefore, this Systematic Literature Review (SLR) study will report the results of SSR reviews in mathematics learning in Indonesia. There are five research questions to be answered regarding trends, designs, subject characteristics, learning materials, and types of intervention and target changes from SSR. Following the PRISMA flow, 561 articles were identified from three databases (Dimensions, ERIC, and SINTA), then through the screening stage, and finally 53 articles were included for review. The results of the review, in the form of data extraction from each article, were mapped and analyzed using quantitative descriptive methods. The results of the study found that (1) the trend of SSR publications has increased significantly, peaking in 2023, despite fluctuations in some years, (2) the ABA reversal is the most dominant SSR design used, (3) the most dominant characteristics of subjects involved in this SSR are sensory disabilities and special-needs schools, (4) the materials most commonly used in SSR are numbers and operations, and (5) interventions in SSR mostly use learning media or technology, and most target changes in specific mathematical skills. These results recommend expanding the application of SSR to various topics and levels with more complex designs and technology-based interventions in real contexts, in order to support inclusive, adaptive, and sustainable mathematics learning.